2018
DOI: 10.3389/fendo.2018.00749
|View full text |Cite
|
Sign up to set email alerts
|

Differential Hepatic Gene Expression Profile of Male Fathead Minnows Exposed to Daily Varying Dose of Environmental Contaminants Individually and in Mixture

Abstract: Environmental contaminants are known to impair reproduction, metabolism and development in wild life and humans. To investigate the mechanisms underlying adverse effects of contaminants, fathead minnows were exposed to a number of endocrine disruptive chemicals (EDCs) including Nonylphenol (NP), bisphenol-A (BPA), Di(2-ethylhexyl) phthalate (DEHP), and a mixture of the three chemicals for 21 days, followed by determination of the liver transcriptome by expression microarrays. Pathway analysis revealed a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 117 publications
2
6
0
Order By: Relevance
“…The results obtained in this study are in agree with previous research showing activation of hepatic stress response after EDCs exposure (Jin et al, 2010a;2010b;Zare et al, 2018). In particular, the modulation of antioxidant defence, the immune response and the possible onset of an apoptotic process were taken into consideration.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained in this study are in agree with previous research showing activation of hepatic stress response after EDCs exposure (Jin et al, 2010a;2010b;Zare et al, 2018). In particular, the modulation of antioxidant defence, the immune response and the possible onset of an apoptotic process were taken into consideration.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, 12-24 h of incubation with BPA caused the upregulation of GSTM in another marine sh, Kryptolebias marmoratus [54]. Similar results were also reported as elevated GST speci c activity in the liver tissues of freshwater species like Pimephales promelas (Zare et al 2018) [55] and Oryzias latipes [56]. In the current study, BPS treatment of Oncorhyncus mykiss hepatocyte culture unveiled the very same response of elevated total GST speci c activity, demonstrating the practicality of the usage of this parameter in the testing of damage of xenobiotic exposure to aquatic animals.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously observed perturbations to male goldfish liver metabolism following EDC exposure alone and in mixture ( Jordan et al, 2012 ). Liver transcriptomics studies have shed light on alterations to lipid metabolism and the hepatic transcriptome following EDC exposure ( Santangeli et al, 2018 ; Zare et al, 2018 ). EDC alter neurotransmitter receptor pathways in brain as well as overall gene expression patterns ( Martyniuk et al, 2006 ; Gore, 2010 ) and polychlorinated biphenyls were observed to affect GnRH gene expression in GT-1 cell lines ( Gore, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…In real-world exposure scenarios, both terrestrial and aquatic species are exposed to mixtures of contaminants, making results from individual exposure studies less applicable in modeling the extent of physiological perturbation induced by environmental contaminant exposures. Mixture studies are important as they more closely mimic the complexity of organisms responses to contaminants, and frequently show that the response is not simply additive ( Jordan et al, 2012 ; Kinch et al, 2015 ; Heys et al, 2016 ; Thrupp et al, 2018 ; Zare et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%